Optimasi Pembuatan Mikrokapsul Kalsium-Alginat-EDTA Sebagai Adsorben Untuk Logam Kadmium - Sani Widyastuti Pratiwi; Ayu Triastuti; Ratna Nurmalasari; Inggis Pinarti (Jurnal Pijar Mipa, 2020)
Cadmium was one of the metals classified in the type of nonessential heavy metal that classified as carcinogenic and is one of the pollutants in the environment, especially water. The content of cadmium in water tends to have very low levels, so certain techniques are needed to determine the level of pre concentration. In the pre concentration technique adsorbents were needed which could absorb cadmium, one of which is calcium-alginate microcapsuleÃÂ modified with EDTA. Calcium-alginate wasÃÂ  modified with EDTA to increase the ability of the microcapsule to absorb cadmium metal. The purpose of this study was to determine the optimum conditions for making Calcium-alginate-EDTA microcapsuleÃÂ in adsorbing cadmium. The stages of this research were optimization of Calcium-alginate-EDTA resin with variable in the form of Calcium chloride concentration (0.05 M; 0.1 M; 0.5 M; 1 M; and 2 M), EDTA mass (0.50 g ; 0.75 g; 1 g; 2 g and 2.5 g) and the concentration of sodium-alginate (0.5%; 1%, 1.5%; 2%, and 3%); Characterization of microcapsuleÃÂ functional groups by infrared spectrophotometry and determination of the retention capacity of Calcium-Alginate-EDTA microcapsuleÃÂ for cadmium absorption by atomic absorption spectrophotometry. The results of infrared characterization showed a change in transmittance in the functional groups C-O dan C-N that occurred in the microcapsuleÃÂ after binding to cadmium metal at wave number 1436.97 cm-1. The optimum conditions for making Calcium-alginate-EDTA resins were in conditions of 0.1 M Calcium chloride concentration, 1% sodium-alginate concentration and EDTA mass 0.75 g EDTA with retention capacity ofÃÂ  Cd was 0.0301 mg/g.